2018
DOI: 10.1016/j.jece.2018.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the lignocellulosic winery wastes behavior during gasification process in fluidized bed: Experimental and theoretical study

Abstract: This work presents studies about the gasification of the lignocellulosic winery wastes in fluidized bed to obtain energy. Based on the exergy analysis, the exergetic improvement potential (IP) and sustainability index (SI) variations with different operational variables were analyzed. IP increases and SI decreases when moisture content, ER and SBR augment. On the other hand, both indexes present contrary behavior with the temperature increasing.Additionally, the kinetic behavior was investigated using a macro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 40 publications
2
5
0
1
Order By: Relevance
“…However, another study 37 with tomato residues not processed and similar to TW from this study reported closer elemental compositions to those obtained in this work. The elemental analysis of WW is in agreement with the literature, 52−55 but some authors detected sulfur contents from 0.03% 55 up to 5.34%, 54 which may be explained by the different processing methods that were applied to obtain the winery wastes. The higher C/N ratios of forestry residues, when compared to the agrowastes, confer them a higher resistance to biological degradation, since microorganisms need a proper balance of those elements.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, another study 37 with tomato residues not processed and similar to TW from this study reported closer elemental compositions to those obtained in this work. The elemental analysis of WW is in agreement with the literature, 52−55 but some authors detected sulfur contents from 0.03% 55 up to 5.34%, 54 which may be explained by the different processing methods that were applied to obtain the winery wastes. The higher C/N ratios of forestry residues, when compared to the agrowastes, confer them a higher resistance to biological degradation, since microorganisms need a proper balance of those elements.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…The HHV obtained for TW and WW were in agreement with the literature, 51,53,54 as well as the values observed for PS and PB. 50 The higher H of PB associated with the slightly higher C, and the lower O contributed to the superior HHV of PB as compared to PS (Tables 1 and 3).…”
Section: Acs Sustainable Chemistry and Engineeringsupporting
confidence: 90%
“…Therefore, an accurate analysis of thermal degreasing kinetics is indispensable. Currently, the research on thermal debinding kinetics mainly focuses on the use of single-reaction models and model-free methods. , Yan et al used the Coats–Redfern method to study the thermal debinding kinetics of copper green parts prepared by the three-dimensional (3D) printing method and obtained the kinetic parameters and reaction order ( n = 1). Salehi et al investigated the pyrolysis kinetics of the binder in the thermoplastic processing of YSZ ceramics by three model-free methods: Ozawa–Flynn–Wall, Kissinger–Akahira–Sunose (KAS), and Friedman.…”
Section: Introductionmentioning
confidence: 99%
“…The mass loss and differential mass loss data are obtained using TGA at low heating rates of 5–100 °C min –1 as a function of time and temperature. The apparent kinetic parameters, viz., activation energy ( E a ) and pre-exponential factor ( A ), are calculated using a number of isoconversional methods and model fitting techniques. Rodriguez and co-workers , evaluated the kinetic behavior of slow pyrolysis of winery waste and agro-residues using Flynn–Wall–Ozawa (FWO) and distributed activation energy model (DAEM) methods. The average E a values for winery wastes including grape marc and stalks were determined to be 123.1 and 189.7 kJ mol –1 , respectively, and those for agro-residues including plum pits, peach pits, and olive pits were determined to be in the range of 104.1–110.2 kJ mol –1 .…”
Section: Introductionmentioning
confidence: 99%